2017
DOI: 10.1002/cmdc.201700358
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Drug Release Abilities of Calcium Carbonate–Gelatin Hybrid Nanocarriers Fabricated via a Self‐Organizational Process

Abstract: In this study, we investigated the drug-releasing behavior of a calcium carbonate (CaCO )-gelatin hybrid nanocarrier, fabricated through a single process using biomimetic mineralization. The organic scaffold (gelatin) of the fabricated nanocarrier is responsible for its capacity to load anionic drugs and for controlling the morphology of the inorganic matrix (CaCO ). We studied the drug-releasing properties of the nanocarrier by investigating the response of the CaCO matrix to acidic conditions. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The calculation results showed that the loading of Exendin4 in PEGDA/HA-4x gel was about 4.17 times and 7.53 times the loading of PEGDA gel in 5 μg/mL and 10 μg/mL Exendin4 solutions respectively, indicating that the introduction of inorganic particles in mineralization process effectively improved the drug loading ability of this kind of biomaterial. 32,33 Then, due to the limited loading capacity of pure hydrogel, the PEGDA gel could only be loaded with limited content of Exendin4, which illustrated the drug loading ability of PEGDA/HA-4x gel in the realistic experimental conditions. From the release curve, the release characteristics of gel immersed in high concentration Exendin4 solution were not significantly different from that of low concentration, while the release of Exendin4 from PEGDA/HA-4x gel had a more stable and longer release cycle, indicating that its potential bone induction ability was better.…”
Section: Discussionmentioning
confidence: 97%
“…The calculation results showed that the loading of Exendin4 in PEGDA/HA-4x gel was about 4.17 times and 7.53 times the loading of PEGDA gel in 5 μg/mL and 10 μg/mL Exendin4 solutions respectively, indicating that the introduction of inorganic particles in mineralization process effectively improved the drug loading ability of this kind of biomaterial. 32,33 Then, due to the limited loading capacity of pure hydrogel, the PEGDA gel could only be loaded with limited content of Exendin4, which illustrated the drug loading ability of PEGDA/HA-4x gel in the realistic experimental conditions. From the release curve, the release characteristics of gel immersed in high concentration Exendin4 solution were not significantly different from that of low concentration, while the release of Exendin4 from PEGDA/HA-4x gel had a more stable and longer release cycle, indicating that its potential bone induction ability was better.…”
Section: Discussionmentioning
confidence: 97%
“…Murai et al used biomimetic mineralization to create a CaCO 3 -gelatin hybrid nanocarrier. Gelatin is used as an organic scaffold to facilitate the loading of anionic drugs and to control the morphology of CaCO 3 minerals (Murai et al, 2017). Drug release from the nanocarrier was inhibited at neutral pH and triggered in acidic microenvironment of the tumor.…”
Section: Cell Deliverymentioning
confidence: 99%
“…DDS is a system that delivers the drugs “in a minimum amount”, “at the right time”, and “to the right place”. Polymer micelles [ 5 , 6 ], dendrimers [ 7 , 8 , 9 ], hydrogels [ 10 , 11 , 12 , 13 ], and mesoporous nanoparticles [ 14 , 15 , 16 ] have been reported as DDS carriers. In addition, vesicles have been used for DDS carriers.…”
Section: Introductionmentioning
confidence: 99%